STRUKTUR MITOS DALAM CERITA RAKYAT “BATU NGANGA BATANGKO” SEBUAH KAJIAN STRUKTURALISME LEVI-STRAUSS - Hasbullah Hasbullah; Rahmin Meilani Putri (CV. ADIBA ASIHA AMIRA, 2023)
This study describes the mythical structure in the folklore of batu nganga batangko in the people of Rhee Loka Village, Rhee District, Sumbawa Regency. The purpose of this study is to identify the shape of miteme-miteme and reveal the meaning of myths in the folklore of batu nganga batangko. This research is a qualitative research with descriptive analysis. Data collection is carried out through observation, interviews, and documentation. Data analysis was carried out on data that were considered to describe the problems raised in this study, utilizing Levi-Strauss's theory of structuralism. The study identified 41 miteme divided into three episodes. In addition, researchers also discovered the role of characters as the driving force of stories, mythical language that is relaxed using colloquial language that remains polite, and the meaning of myths that teach us to always have a spirit of life